1994
DOI: 10.1007/bf01406502
|View full text |Cite
|
Sign up to set email alerts
|

Can lacerations of the thoraco-lumbar dura be predicted on the basis of radiological patterns of the spinal fractures?

Abstract: Encroachment upon the spinal canal, separation of the pedicles, associated fractures of the laminae are assumed to be related to dural lacerations consequent to burst fractures of the thoracolumbar spine. Owing to the possible occurrence of early or delayed complications of meningeal discontinuations, the predictive value of these signs has been analyzed in a consecutive series of 50 patients, who were submitted to surgery. Dural tears were found to occur at a rate of 60%, without any statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
0
7
0
3
Order By: Relevance
“…Although Pau et al 14 had also reported that encroachment of the spinal canal, separation of the pedicles, and laminar fractures were related to dural lacerations subsequent to spinal burst fractures, they concluded that none of these factors were significant statistically. However, in our study, 4 findings (except the extent of epidural hemorrhage) were statistically significant in identifying dural tears.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although Pau et al 14 had also reported that encroachment of the spinal canal, separation of the pedicles, and laminar fractures were related to dural lacerations subsequent to spinal burst fractures, they concluded that none of these factors were significant statistically. However, in our study, 4 findings (except the extent of epidural hemorrhage) were statistically significant in identifying dural tears.…”
Section: Discussionmentioning
confidence: 98%
“…9,12,[19][20][21][22][23][24] Therefore, a number of observations suggest that knowledge of the actual presence of dural tears in patients with spinal fractures could represent a relevant adjunct to the rationale for optimal management. 9,14,16 Identification of dural tears through imaging techniques or surgical approach is also important for preventing further neurologic injury and promoting neurologic recovery during the treatment of spinal burst fractures. If radiologists mention the possibility of a dural tear in the report of spine MR imaging, the surgeons will make an effort to identify the presence or absence of a true dural tear, even of very small size around fracture sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not always possible to predict by preoperative investigation whether a patient without neurologic deficit, but with a greenstick lamina fracture, has a dural tear and/or cauda equina entrapment [5,6,15]. Although identification of dural tears or entrapped cauda equina before surgery is important, direct visualization of dural tears is often difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, dural tears and cauda equina entrapment are very difficult to diagnose clinically or radiographically before surgery [5,6]. To date, dural tears have been traditionally diagnosed using conventional myelography, which cannot be performed unless the patient can tolerate the procedure without altering his/her neurologic status during the examination [7].…”
Section: Introductionmentioning
confidence: 99%